2017
DOI: 10.1111/phpp.12282
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive red and near‐infrared wavelength‐induced photobiomodulation: promoting impaired cutaneous wound healing

Abstract: SUMMARYThe innumerable intricacies associated with chronic wounds have made the development of new painless, noninvasive, biophysical therapeutic interventions as the focus of current biomedical research. Red and near-infrared light-induced photobiomodulation therapy appears to emerge as a promising drug-free approach for promoting wound healing, reduction in inflammation, pain and restoration of function owing to penetration power in conjunction with their ability to positively modulate the biochemical and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 45 publications
0
53
0
2
Order By: Relevance
“…IRA, as well as the red part of the visible spectrum, has been used in phototherapy for many years. It is administered as coherent (laser) or incoherent (various types of lamps) radiation, exploiting the photobiostimulatory effects to treat a lot of conditions of the skin, subcutaneous tissue and other tissues by accelerating wound healing, reducing inflammation and, in general, stimulating metabolism (see for instance [33,34]).…”
Section: Iramentioning
confidence: 99%
“…IRA, as well as the red part of the visible spectrum, has been used in phototherapy for many years. It is administered as coherent (laser) or incoherent (various types of lamps) radiation, exploiting the photobiostimulatory effects to treat a lot of conditions of the skin, subcutaneous tissue and other tissues by accelerating wound healing, reducing inflammation and, in general, stimulating metabolism (see for instance [33,34]).…”
Section: Iramentioning
confidence: 99%
“…It has been demonstrated that polarized light at 590 nm stimulates angiogenesis and growth factors, while at 830 nm it activates the cells involved in wound healing; a dose of 20 J/cm 2 stimulates increased collagen deposition, an increase in myofibroblasts and a better ultrastructural organization of the wound healing process [9][10][11][12][13][14].…”
Section: Polarized Lightmentioning
confidence: 99%
“…Red light (630‐700 nm) has the greatest tissue penetration of the visible spectrum, reaching the entirety of the dermis at a depth of up to 6 mm . Light emitting diode‐red light (LED‐RL) phototherapy has been demonstrated to be safe and effective for wound healing, hair regrowth, acne vulgaris, skin rejuvenation, oral mucositis, skin cancers and premalignant skin lesions . LED‐RL activates cell signaling pathways that modulate skin cell function and translate to clinical benefits such as tissue regeneration and skin rejuvenation .…”
Section: Introductionmentioning
confidence: 99%